Aberrant Volume-Wise and Voxel-Wise Concordance Among Dynamic Intrinsic Brain Activity Indices in Parkinson’s Disease: A Resting-State fMRI Study - Tian, Yuan; Chen, Hai-Bo; Ma, Xin-Xin; Li, Shu-Hua; Li, Chun-Mei; Wu, Shao-Hui; Liu, Feng-Zhi; Du, Yu; Li, Kai; Su, Wen (Frontiers in Aging Neuroscience, 2022)
Researchers using resting-state functional magnetic resonance imaging (rs-fMRI) have applied different static regional measurements to study the intrinsic brain activity (IBA) of patients with Parkinson's disease (PD). However, the dynamic nature of brain activity suggests the presence of concordance between various regional indices, leading us to explore volume-wise and voxel-wise concordance in this study. This study used a sliding time window approach and included 31 healthy controls (HCs) and 57 PD patients to calculate the volume-wise (across voxels) and voxel-wise (across periods) concordance. This allowed us to compare the dynamic characteristics of frequently used metrics such as degree centrality (DC), global signal connectivity (GSC), voxel-mirrored heterotopic connectivity (VMHC), the amplitude of low-frequency fluctuations (ALFF), and regional homogeneity (ReHo). We compared the differences between groups of concordance indicators and analyzed the relationship between concordance values and clinical/neuropsychological assessments in PD patients. We found that, compared with HCs, PD patients had lower volume concordance in the whole brain and lower voxel-wise concordance in the posterior cerebellar lobe, cerebellar tonsils, superior temporal gyrus, and supplementary motor region. We also found negative correlations between these concordance alterations and patients' age. The exploratory results contribute to a better understanding of IBA alterations and pathophysiological mechanisms in PD.